Some aspects of teaching oral consecutive interpretation in higher education instruction - Matassova, I.N.; Horoshilova, S.P. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
This article represents the author’s approach to teaching the course of oral consecutive interpretation in higher education institutions. Having reviewed several definitions of the concept of «translation» presented by the masters of this type of activity, the author further delves into the study of the concept and main characteristics of oral consecutive interpretation. The subtypes of this type of interpretation, including at-sight translation, phrasal interpreting, consecutive interpretation without notation, consecutive interpretation with notation, are listed. Subtypes of oral consecutive interpretation are illustrated by a system of exercises aimed at developing students’ skills necessary for oral transfer of messages from English into Russian and vice versa. In addition to several such exercises, the author also provides for methodological recommendations for working out a particular type of interpretation, and also gives a list of alternative exercises, the use of which can significantly expand the scope of professional skills and abilities of students — future translators. Exercises are taken from the «Practicum on oral translation» published by the author two years ago, and are successfully used by her as a teacher at the interpretation lessons with university students.
Жоо-да ауызша ілеспелі аударманы оқытудың кейбір қырлары
Некоторые аспекты преподавания устного последовательного перевода в вузе
Keywords: translation; oral consecutive interpretation; translator; interpreter’s notation; at-sight translation; text; exercise; student